Integrasi Penerapan Model Problem Based Learning (PBL) dengan Model Pembelajaran Connecting, Organizing, Reflecting, Extending (CORE) terhadap Kemampuan Pemecahan Masalah Matematika Calon Guru SD - Latri, Latri; Juhari, Agusalim; Patta, Rahmawati (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
This research aims to explain the effectiveness of integrating the PBL model with the CORE model on the mathematical problem solving abilities of prospective elementary school teachers. Pre-experimental research with One-Group Pretest Posttest Design to achieve research objectives. The population in this study were all PGSD students at Makassar State University consisting of 3 classes. The experimental units were taken using cluster random sampling, from 3 selected classes, namely BC.212 as the experimental class consisting of 30 people. The data collection techniques used were learning outcomes tests, observation sheets, and student response questionnaires. Student activity and response data were analyzed using descriptive statistical analysis, while student mathematics learning outcomes data used inferential statistical analysis. The results of the research show that the integration of the PBL model with the CORE model is effectively applied in mathematics learning, Geometry and Learning material in terms of: 1) the average score of mathematics learning outcomes in the aspect of students' Problem Solving Ability in the posttest is greater than 75 (KKM), namely 83, 4 of the ideal scores of 100 are in the High category. The normalized gain obtained is 0.73, which is in the High classification; 2) the average student activity score of 3.56 is in the very active category; 4) the average percentage of student responses was 85.45% in the positive category.